Repetitive Transcranial Magnetic Stimulation With H-Coil in Alzheimer's Disease: A Double-Blind, Placebo-Controlled Pilot Study - Leocani, Letizia; Dalla Costa, Gloria; Coppi, Elisabetta; Santangelo, Roberto; Pisa, Marco; Ferrari, Laura; Bernasconi, Maria Paola; Falautano, Monica; Zangen, Abraham; Magnani, Giuseppe; Comi, Giancarlo (Frontiers in Neurology, 2021)
Focal repetitive transcranial magnetic stimulation (rTMS) has been applied to improve cognition in Alzheimer’s disease (AD) with conflicting results. We applied rTMS in AD in a pilot placebo-controlled study using the H2-coil, suitable for targeting wider and deeper neuronal structures compared with standard focal coils. Thirty patients were randomized to sham or real 10 Hz rTMS simultaneously over frontal-parietal-temporal lobes bilaterally. Each patient underwent 3 sessions/week for 4 weeks, followed by 4 weeks with maintenance treatment (1 session/week). Primary outcome was improvement of ADAS-cog at 4 and 8 weeks compared with baseline. A trend towards an improved ADAS-cog score over time was observed for patients undergoing real rTMS, with actively treated patients experiencing a mean decrease of -1.01 points at the ADAS-Cog scale score per time point (95% Cis -0.02- -3.13, p< 0.04). This trend was no longer evident 2 months after the end of treatment. Real rTMS showed no significant effect on MMSE and BDI changes over time. These preliminary findings suggest that rTMS with H-coil is feasible and safe in patients with probable AD and might provide beneficial, even though transient, effects on cognition. This study prompts larger studies in the early stages of AD, combining rTMS and cognitive rehabilitation.